2022
DOI: 10.3390/ijms23020947
|View full text |Cite
|
Sign up to set email alerts
|

The Peptide A-3302-B Isolated from a Marine Bacterium Micromonospora sp. Inhibits HSV-2 Infection by Preventing the Viral Egress from Host Cells

Abstract: Herpesviruses are highly prevalent in the human population, and frequent reactivations occur throughout life. Despite antiviral drugs against herpetic infections, the increasing appearance of drug-resistant viral strains and their adverse effects prompt the research of novel antiherpetic drugs for treating lesions. Peptides obtained from natural sources have recently become of particular interest for antiviral therapy applications. In this work, we investigated the antiviral activity of the peptide A-3302-B, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The respiratory syncytial virus (RSV) A2 strain (ATCC ® VR-1540), the human rotavirus (HRoV) strain Wa (ATCC ® VR-2018), and the herpes simplex virus type 2 (HSV-2) strain MS (ATCC ® VR-540) were propagated in Hep2, MA104, and Vero cells, respectively [ 67 , 68 ]. The human influenza virus type A strain A/New Caledonia/20/99 (FluVA-H1N1; Italian National Institute of Health) was propagated in canine kidney epithelial MDCK cells (ATCC ® NBL-2) with a culture medium supplemented with 0.5 µg/mL of porcine pancreas trypsin (Sigma-Aldrich; St. Louis, MO, USA) [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The respiratory syncytial virus (RSV) A2 strain (ATCC ® VR-1540), the human rotavirus (HRoV) strain Wa (ATCC ® VR-2018), and the herpes simplex virus type 2 (HSV-2) strain MS (ATCC ® VR-540) were propagated in Hep2, MA104, and Vero cells, respectively [ 67 , 68 ]. The human influenza virus type A strain A/New Caledonia/20/99 (FluVA-H1N1; Italian National Institute of Health) was propagated in canine kidney epithelial MDCK cells (ATCC ® NBL-2) with a culture medium supplemented with 0.5 µg/mL of porcine pancreas trypsin (Sigma-Aldrich; St. Louis, MO, USA) [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…The human influenza virus type A strain A/New Caledonia/20/99 (FluVA-H1N1; Italian National Institute of Health) was propagated in canine kidney epithelial MDCK cells (ATCC ® NBL-2) with a culture medium supplemented with 0.5 µg/mL of porcine pancreas trypsin (Sigma-Aldrich; St. Louis, MO, USA) [ 69 ]. After propagation, the obtained viral progenies were clarified out of cell debris, aliquoted, and stored at −80 °C prior to virus titration by standard plaque assay or focus reduction assay, dependently on the viral agent considered [ 67 , 68 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of aiming at the entire viral life cycle, other cell-based assays have been developed to screen viral inhibitors that target specific steps of the infectious process [ 171 , 172 , 173 ]. For instance, classic methods to screen inhibitors of viral entry include cell–cell fusion assays and cell–virus fusion assays.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Transmission electron microscopy revealed that this peptide diminishes the viral spread by containing the herpetic virions escape from the infected cells and suppresses the herpetic cytopathic effect. Furthermore, it is potent against acyclovir-resistant HSV-2 [ 145 ].…”
Section: Novel Drugs and Nano Moleculesmentioning
confidence: 99%